Adiposity is inversely related to insulin sensitivity in relatively lean Chinese adolescents: a population-based twin study(1)(2)(3) - Ouyang, Fengxiu (American Society for Nutrition, 2010)
Background: Adolescence is a critical period for rising adiposity and falling insulin sensitivity (IS), but the independent relation between adiposity and IS remains understudied. Objective: The objective was to examine which adiposity measures are most strongly associated with IS in nondiabetic adolescents, whether sex-difference exists, and to what degree genetic or environmental factors affect the adiposity-IS relation. Design: The study included 1613 rural Chinese adolescents (888 males) aged 13–20 y from a population-based twin cohort. We used graphic plots and linear mixed models to examine the relation of anthropometric and dual-energy X-ray absorptiometry–based measures of adiposity with IS [QUantitative Insulin-sensitivity ChecK Index (QUICKI), fasting serum insulin (FSI), homeostasis model assessment of insulin resistance (HOMA-IR)] and structural equation models to estimate genetic/environmental influences on these associations. Results: In graphic analyses, participants in the highest quintile (quintile 5) of waist circumference (WC) and percentage body fat (%BF) had the lowest QUICKI and the highest FSI and HOMA-IR values for all age-sex groups. In regression models adjusted for age, Tanner stage, zygosity, and physical activity, all adiposity measures showed inverse associations with IS in both sexes, but WC explained the largest fraction of variance in IS measures (10–14%). Of the phenotypic correlations between adiposity measures and IS (−0.28 to −0.38), 74–85% were attributed to shared genetic factors and 15–26% to common unique environmental factors in both sexes. Conclusions: In these relatively lean Chinese adolescents, WC and %BF (quintile 5) are the adiposity measures most consistently and strongly associated with decreased IS in both sexes. To a large degree, shared genetic factors contribute to this association.